Studi Kualitatif Strategi Koping Perawatan Diri Pada Pasien Post Percutaneous Coronary Intervention (PCI) - Nadia, Sri; Wati, Del Fatma; Hasnita, Evi; Febrina, Wiwit; Wahyuni, Aria (REAL in Nursing Journal, 2022)
Background: Coronary Heart Disease is a disease of the coronary arteries that are in charge of  supplying blood supply to the heart muscles so that it can cause a heart attack. Prevention In order to prevent the recurrence of heart attacks in patients with coronary heart disease, they need to carry out massive self-care with the existence of coping strategies that can act as individual responses to the stressors they face. The purpose of this study was to explore how self-care coping strategies in post-Percutaneous Coronary Intervention (PCI) patients. Methods: This study used a phenomenologcal approachwith a qualitative design, and then the data were analyze  used The collaizi method. Research informants were taken using purposive sampling technique, totaling 7 people who did re-control at the Cardiology Polyclinic of RSUD Dr. Achmad Mochtar Bukittinggi. Data were collected through in-depth interviews and field notes. Results: The results of this study identified two themes, namely: problem-focused coping strategy and emotion-focused coping strategy. It can be concluded that the form of coping strategies carried out by post-Percutaneous Coronary Intervention (PCI) patients at RSUD Dr. Achmad Mochtar Bukittinggi varies and the Problem Focused Coping strategy is the main strategy used. There are also participants who use Emotion-Focused Coping strategies. Conclusion: It is recommended that the results of this study can add and provide input as well as reference material for health workers, especially nurses, in providing nursing interventions in the management of chronic diseases during treatment.Keywords: Coping Strategies, Self Care, Coronary Heart Disease, Percutaneous Coronary Intervention (PCI)